Partnership in the Lease of Cults in Greek Antiquity - Sokolowski, F. (Harvard theological review, 1957)
We are in possession of a Number of documents (inscriptions and papyri) relating to the lease of priesthoods in Greece and Egypt, dating from the fifth century B.C. to late Roman times. That curious practice, similar in some respect to the holding of Church benefices in the Middle Ages, has been studied by different scholars, but without agreement on many substantial points. Before the second World War K. Wilhelmson and M. Segre dedicated very important studies to the problem, advancing considerably the interpretation of the sources. In my Lois Sacrées of Asia Minor I collected many specimens of these documents and tried my best to promote their understanding. But nobody has sought to link the sale of cults in Greece with the same practice, as it is well attested through the papyri, in Ptolemaic and Roman Egypt. Meanwhile the inscriptions and the papyri, put together, not only fill the lacunas existing in both fields of documentation, but contribute to elucidate the legal side of the practice itself. With the recent publication of the study of M. Talamanca on auction in the classical world, the task has now become easier. Unfortunately the author does not utilize the abundant epigraphical material on our subject. I should like to endeavor to supply in part this need.